Review of 5th Generation Mobile Communication Technologies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
5G is the next-generation network technology which  promises  exponentially higher bandwidth and lower latency to serve a wide range of consumer and commercial Internet of Things applications (IoT). With its next-generation network architecture, 5G has the ability to serve hundreds of new consumer and industrial applications. When speed and throughput are exponentially higher than current networks, the potential for 5G seem almost unlimited. 5G isn't only about "larger, faster, and better" networks. It's all about enabling a wide range of new services and use cases that affect almost every part of our life. However, 5G-enabled applications must be delivered securely in order to realise their full potential, and security challenges must be addressed at the network core from the start in order to protect both networks and customers. Some of the most fundamental concerns about 5G networks are discussed in this study. The paper can enlighten its readers on what is expected of 5G network, its architecture and what are the basic security issues involved in it.